Psychological Distress, Terrorist Involvement and Disengagement from Terrorism: A Sequence Analysis Approach - Corner, Emily (Journal of quantitative criminology, 2020)
This paper utilizes probability-based modelling to unpack the complex and multifaceted individual, sociological, and psychological processes present within terrorist groups which may affect an individual’s psychological wellbeing. We outline the predictors of the onset of psychological distress across three phases of terrorist involvement (engagement, disengagement, and post-disengagement).